Pengaruh Leverage, Likuiditas, Aktivitas, dan Ukuran Perusahaan terhadap Profitabilitas (Studi Empiris pada Perusahaan Penyedia Jasa Kesehatan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Nabilah Amanah; Slamet Mudjijah (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to determine the influence of Leverage, Liquidity, Activity and Company Size on Profitability in health service provider companies listed on the IDX for the 2019 - 2023 period. This research was conducted using secondary data, namely financial reports. The sampling technique used was purposive sampling. Of the 14 companies, only 10 companies consistently publish financial reports every year. The analysis model used is multiple linear regression analysis which was tested with IBM Statistics Product and Solution (SPSS) version 26. The research results show that partial leverage has a negative and insignificant effect on profitability. Activity has a positive and significant effect on profitability. Liquidity and Company Size have no effect on Profitability. Meanwhile, simultaneously, Leverage, Liquidity, Activity and Company Size influence Profitability.